Transformasi Sosial Melalui Program Keluarga Harapan: Analisis Dakwah Transformatif di Desa Barugaya, Takalar - Junaedi (Danudirja Setyabudi Nusantara, 2025)
This research critically examines the strategy of the Social Service in implementing the Family Hope Program (PKH) in Barugaya Village, East Polongbangkeng District, Takalar Regency, with a specific focus on the transformative da'wah approach. The research, conducted using a qualitative approach, gathered primary data through interviews, observations, and documentation from PKH assistants, PKH Coordinators, beneficiaries, and other related parties. The findings revealed that the PKH program in Barugaya Village provides crucial cash assistance for education and health. The implementation of this program, which includes a data verification process, socialization, group meetings, and the distribution of assistance, is designed to heighten community awareness of the importance of education and health to break the cycle of poverty. The research underscores the necessity for PKH assistants to possess advanced social assistance skills to bolster beneficiaries' capacity and ensure maximum impact. The implications of this research underscore the transformative da'wah's role in PKH, which focuses on providing material assistance and plays a pivotal role in community empowerment through active mentoring. The transformative da'wah approach, focusing on community empowerment, fortifies the community's social base and hastens the achievement of sustainable social change. As a result, the PKH program emerges as a potent tool in enhancing the community's quality of life through education and health, and in breaking the chain of poverty.